A BLUEPRINT FOR A NEW AND REVOLUTIONARY SPIRITUAL PATH - Bilimoria, Purushottama (Journal of Dharma, 1989)
The idea of a total and radical change, not only at the individual but also at the level of humanity at large, for the bettermentof our times, was taking shape in me for sometime. We all know how grave the modern day malaisé is and the dangers that loom over our heads threatening the peace of our times. A warning from Sri Aurobindo, the Indian sage-philosopher, given some thirty years ago, points a way out: "It is for the men of our days and, at the most, of tomorrow to give the answer. For, too long a postponement or too continued a failure will open the way to a series of increasing catastrophes which might create a too prolonged and disastrous confusion and chaos and render a solution too difficult or impossible; it might even end in something like an irremediable crash not only of the present world civilisation but of all civilisation. A new, a difficult and uncertain beginning might have to be made in the midst of the chaos and ruin after perhaps an extermination on a large scale, and a more successful creation could be predicted only if a way was found to develop a better humanity or perhaps a greater superhuman race." (The Ideal of Human Unity pp. 389-390).